MANAJEMEN ZIS (ZAKAT, INFAK, SEDEKAH) DALAM PEMBINAAN DAN PENGEMBANGAN POTENSI ANAK YATIM DI YAYASAN YATIM MANDIRI LAMPUNG - Setiawati, Rini (Universitas Islam Negeri Raden Intan Lampung, 2018)
Maintenance of orphans that exist today, especially in Indonesia is often understood by some of the general public is limited to the provision of funds donations, so that orphans who have grown up still characterless dependence on the help of others. Therefore, it takes a good concept in this case, namely the ideal concept in the maintenance of orphans who make orphans as human resources who excel and berakhlaq noble. However, there are still many problems that need to be resolved. For example, the education of orphans who often end up in 'dropouts' while education assistance for them is very much, which should orphans be able to compete in the world of academics and work sebgaimana children his age. Not to mention the problem of orphans is often the victim of violence in the community, as well as the management of orphan's very bad property in this country, so much of the wealth or social aid for missing orphans